Mengintegrasikan Konten Kimia Kontekstual tentang Reaksi Redoks dalam Pemeliharaan Sasis untuk Program Keahlian Teknik Kendaraan Ringan - Santi Deva; Sjaeful Anwar; Ijang Rohman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the relevance and integration of contextual chemistry content, particularly focusing on redox reactions in the context of corrosion in automotive chassis maintenance, into the vocational education curriculum of Light Vehicle Engineering (Teknik Kendaraan Ringan Otomotif/TKRO) programs. Utilizing the Qualitative Content Analysis (QCA) method, this research examines curriculum documents, IPAS (Ilmu Pengetahuan Alam dan Sosial) modules, and interviews with both science and vocational teachers to identify gaps between chemistry teaching and vocational practices. The results reveal that essential chemical concepts such as oxidation-reduction reactions, electrochemistry, and corrosion science are currently absent or underrepresented in the general science curriculum. These omissions hinder students’ understanding of crucial maintenance procedures related to metal degradation, material selection, and protective treatments. The study proposes a contextualized chemistry material outline to bridge this gap, enabling vocational students to apply scientific principles effectively in real-world automotive settings. Findings from this study advocate for the incorporation of redox and electrochemical content in vocational science education to enhance both conceptual understanding and technical competency.